2022
DOI: 10.3389/fphys.2022.869903
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Swimming Training Session on Selected Saliva Components in Youth Swimmers

Abstract: Exercise may induce many changes in biochemical parameters of the saliva. Thanks to non-invasive access, saliva can be used as a diagnostic material in physical activity monitoring. The aim of the study was comparison of selected salivary components in swimmers before and after training session. 40 male subjects aged 12–15, out of whom 30 were competitive swimmers and 10 control were involved in the study. Salivary samples were collected from all subjects in the morning, and in the afternoon; from the swimmers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Correspondingly, in a study with a larger number of subjects, Ancy et al (2021) reported the lowest levels of SA amongst healthy subjects with no significant effects of age or gender on these outcomes [14]. Other reports indicate the lack of an association between salivary SA among other groups of subjects evaluated after swimming representing physical exertion [21] or children with Down's syndrome [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, in a study with a larger number of subjects, Ancy et al (2021) reported the lowest levels of SA amongst healthy subjects with no significant effects of age or gender on these outcomes [14]. Other reports indicate the lack of an association between salivary SA among other groups of subjects evaluated after swimming representing physical exertion [21] or children with Down's syndrome [22].…”
Section: Discussionmentioning
confidence: 99%
“…Available in the literature are several previous reports examining SA and sialidase in the saliva and blood samples amongst patients of different ages [11][12][13] including those stratified by their health status [14][15][16][17][18][19][20][21]. These studies have utilized several analytical approaches for SA analysis [12,[14][15][16][17][18][19][20][21][22]. Whereas these previous investigations report salivary SA levels, the results are from one sampling event and do not report evaluations over time.…”
Section: Introductionmentioning
confidence: 99%
“…Yasuda et al ( 55 ) found that 11 male cyclists had increased sAA activity after exercising at 60% of peak oxygen uptake in a thermoneutral environment. Another study showed increased sAA activity in adolescent swimmers after swimming lessons ( 56 ). Gill et al ( 53 ) also found that 23 ultra-endurance runners had increased sAA activity after a 230-km multi-stage ultramarathon in hot environmental conditions (32– 40°C).…”
Section: Discussionmentioning
confidence: 99%
“…To satisfying the demand for non-invasive sensors, other body liquids should be involved in monitoring training load in athletes. Among all biological liquids for monitoring training load, saliva seems to be one of the most important diagnostic materials for tools in medical sciences [6][7][8]. One of the significant features of saliva is that the lactate concentration shows a good correlation between blood and saliva [9].…”
Section: Introductionmentioning
confidence: 99%
“…One of the significant features of saliva is that the lactate concentration shows a good correlation between blood and saliva [9]. At the same time, despite the attempts to find alternative saliva biomarkers attributed to exercise training, lactate is still an important issue in clinical diagnosis and sports medicine [6,10].…”
Section: Introductionmentioning
confidence: 99%